Perbedaan Peningkatan Kemampuan Koneksi Matematis Siswa SMP melalui Pembelajaran Berbantuan Puzzle dan Geogebra Ditinjau Berdasarkan Gender - Ayu Mentari; Bobbi Rahman; Surya Wijaya (Institut Agama Islam Negeri Curup, 2020)
Based on TIMSS 2011 and PISA 2018, mathematical connection ability of Indonesian students has not been optimal. Some of questions in TIMSS and PISA measured the mathematical connections ability. Needed the instructional media to increase mathematical connection ability, such as puzzle and GeoGebra. In addition, gender also affects students' mathematical ability. This study aims to investigate differences in mathematical connection abilities between students who learning by puzzle and GeoGebra, investigate differences in mathematical connection abilities between male and female students, and investigate interactions between instructional media and gender. This research was a quasi-experiment which used nonequivalent control group design. The samples were students of class VIII-A and VIII-B in Junior High School of 1 Tangerang City. The instruments in this research consisted of test items, such as pretest and posttest. Hypotheses test through parametric test (ANOVA Two Tail). Based on ANOVA Two Tail-test result, showed that there is difference increase in mathematical connection ability students who learning by GeoGebra and puzzle. Then, there is no difference increase mathematical connections ability between male and female students. The factors of instructional media and gender do not equally affect the increase of mathematical connection ability.